Іноземна мова в процесі євроінтеграції - Ткаченко, Наталія Дмитрівна (My University, 2009)
В статті розглядаються деякі результати введення європей¬ських стандартів організації учбового процесу, а саме введення модульної системи розподілу учбового матері¬алу та контролю за його засвоєнням студентами. Описуються методичні засоби підвищення якості знань студентів.

The articlr considers some results of introducing the European standards of the learning process organization, more specifically, the introduction of the module system in distributing the material studied and control after its learning by the students. Some methodological means to raise the quality of the student’s knowledge are described.
Keywords: вища освіта; організація процесу навчання; модульна система; методи; якість знань; higher education; learning process organization; module system; methods; knowledge quality